Odpowiedzi

2010-01-18T17:40:43+01:00
A)¹₃y=x-3 / *3
y = 3x-9

b) 3(x-y)=2x / :3
x-y = 2x/3
-y = 2x/3 - x / :(-1)
y = -2x/3 + 3x/3
y = x/3

c) ²₃x =₃3/4y / *3
2x = 9/4y / :2x
1 = 9/8xy / *y
y = 9/8x

d) 4x+2y=1
2y = 1-4x / 2
y = ½ - 2x

e) 6x-2/3y=2 / *3
-2y = 6 - 18x / :(-2)
y = -3+9x
y = 9x-3
1 5 1
2010-01-18T17:41:08+01:00
A)¹₃y=x-3/×3
y=3(x-3)
y=3x-9

b) 3(x-y)=2x
3x-3y=2x
3x-2x=3y
x=3y/÷3
¹/₃x = y

c) ²₃x =₃3/4y - nie wiem co to ta trojka mala po prawej stronie rownania
²₃x =3¾y
⅔x=¹⁵/₄ y /÷ ¹⁵/₄
8/45 x = y

d) 4x+2y=1
2y=1-4x/÷2
y = ½ - 2x

e) 6x-2/3y=2
6x-2 = 2/3 y /* ³/₂
9x-3 = y
1 5 1